مسئولیتِ فوجداری:قوانینِ وضعیہ اور شریعتِ اسلامیہ کا تقابلی جائزہ: A Jurisprudential and legal analysis of the reasons for the termination of punishment in Islamic Criminal law (Khairulummah, 2023)
The Islamic law advocates social justice, emphasizes the status quo of a system of justice, and devises a mechanism.Consequently, in this regard, Islamic Law discusses retalition /qisas , hudood (punishments prescribed by Allah & his prophet), and to give Punishments (left to the discretion of court). Islam declares retalition /qisas as a surety of life and mentions the status quo of a system of justice as the purpose of the revelation of the Prophets and Messengers. In Islamic regulation, hudood and retaliation cannot be suspended or removed. Even as the Islamic system of justice wherein insists on paying for the rights of the victim, It additionally prevents aggression and cruelty in enforcing the regulation on the perpetrator and binds the wrongdoer or his guardians or law enforcement organizations to criminal jurisdiction. Therefore, this research article describes a systematic and comparative evaluation of Jurisprudential and legal review of the causes of exemption from serving a punishment in Islamic criminal law with reference to Al-Tashri’ul Jinai by Abdul Qadir uda.